Ответ(ы) на вопрос:
Пусть (x+3)^2=t, тогда:
[latex]t^2+2t-8=0 \\ D=4+4*8=36 (6), \\ t_1=2, t_2=-4.[/latex]
С учетом замены:
[latex](x+3)^2=2 \\ [/latex]
[latex]x^2+6x+7=0 \\ D=8(2 \sqrt{2} ), x_1= \sqrt{2} -3, x_2=- \sqrt{2} -3 \\ (x+3)^2=-4[/latex] - Решений нет.
Ответ: [latex]x_1= \sqrt{2}-3, x_2=- \sqrt{2} -3.[/latex]
(x+3)^4+2*(x+3)^2-8=0
Пусть (x+3)^2=t
t²+2t-8=0
По теореме Виета:
[latex] t_{1}=-4(не подх). [/latex] [latex] t_{2}=2 [/latex]
(x+3)^2=2
x²+6x+7=0
D=36-28=8
√D=2√2
[latex] x_{1}= \frac{-b-\sqrt{D}}{2a}= \frac{-6-2\sqrt{2}}{2}= \frac{2*(-3-\sqrt{2})}{2}=-3- \sqrt{2} [/latex]
[latex] x_{2}= \sqrt{2}-3 [/latex]
Ответ:[latex]-3-\sqrt{2};\sqrt{2}-3[/latex]
Не нашли ответ?
Похожие вопросы